Antioxidant, antimicrobial and GC-MS analysis of essential oil from Cyperus Corymbosus rottb. rhizome - A. N. SANTHOSHKANNADA; M. K. MAHESH; P. HARIPRASAD (International Journal of Pharma and Bio Sciences, 2019)
The present study was aimed to analyze the antioxidant and antimicrobial activity of essential oil (EO) from the rhizome of Cyperus corymbosus Rottb. Further biological activity was correlated with its chemical constituents. The total phenol content present in EO was determined as 5.87 mg GAE/g EO. The EO recorded maximum inhibition of DPPH radicals (26.0 %) at 10% concentration with IC50 value of 21.46 %. Similarly, ABTS radical scavenging capacity of EO was found to be 30.7% at 10% concentration, and IC50 value was 16.04 %. The disc diffusion assay performed to analyze the antimicrobial activity of EO. Among the three (Escherichia coli, Staphylococcus aureus and Salmonella abony) bacterial species tested, Staphylococcus aureus was found to be highly susceptible to EO, which recorded the highest of 2.3 mm zone of inhibition at 10% concentration of EO. Similarly, A. briselinesis was found more susceptible, which recorded a 2.75 mm zone of inhibition at 10% concentration of EO. E. coli was found resistant to EO, which recorded least of 0.5 mm zone of inhibition against highest concentration tested. The GC/MS studies of EO of C. corymbosus rhizome indicates, presence of 42 different chemical compounds like Vulgarone-B - (27.04%), Nootkatone - (17.47%), Caryophyllene oxide - (15.07%), etc. This work revealed the potential of C. corymbosus as a source of phyto-molecules for medicinal and pharmaceutical applications.